2020
DOI: 10.3389/fnins.2020.543802
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Changes in Blepharospasm: A Cortical Thickness and Diffusion Tensor Imaging Study

Abstract: White matter abnormalities in blepharospasm (BSP) have been evaluated using conventional intra-voxel metrics, and changes in patterns of cortical thickness in BSP remain controversial. We aimed to determine whether local diffusion homogeneity, an inter-voxel diffusivity metric, could be valuable in detecting white matter abnormalities for BSP; whether these changes are related to disease features; and whether cortical thickness changes occur in BSP patients. Diffusion tensor and structural magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…However, we did not find any significant differences in brain WM network measures at both global ( E glob , L p , and modularity) and regional ( E nodal ) levels between BSP and HFS patients, suggesting that abnormal topological organization in BSP may be correlated with excessive facial motor activity. We postulated that facial hyperkinesia‐related brain network alterations in these patients might be due to the increase in facial activity and secondary plastic changes in the brain WM; this hypothesis is supported by a prior study showing the presence of plastic changes in multiple WM tracts that mainly connect the cortices, basal ganglia, thalamus, and brainstem in patients with BSP 16 . Unfortunately, we did not find any correlations between global and regional properties and the severity/duration of BSP and HFS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, we did not find any significant differences in brain WM network measures at both global ( E glob , L p , and modularity) and regional ( E nodal ) levels between BSP and HFS patients, suggesting that abnormal topological organization in BSP may be correlated with excessive facial motor activity. We postulated that facial hyperkinesia‐related brain network alterations in these patients might be due to the increase in facial activity and secondary plastic changes in the brain WM; this hypothesis is supported by a prior study showing the presence of plastic changes in multiple WM tracts that mainly connect the cortices, basal ganglia, thalamus, and brainstem in patients with BSP 16 . Unfortunately, we did not find any correlations between global and regional properties and the severity/duration of BSP and HFS.…”
Section: Discussionsupporting
confidence: 55%
“…Ramdhani and colleagues found that gray matter changes were accompanied by more widely observed WM abnormalities in patients with nontask‐specific dystonia (BSP and cervical dystonia) than in those with task‐specific dystonia (writer's cramp and laryngeal dystonia), which are located mainly in the corpus callosum, anterior limb/genu of the internal capsule, brainstem, cerebellum, thalamus, WM of the middle/inferior frontal gyrus, primary sensorimotor cortex, and inferior temporal gyrus 15 . A prior diffusion tensor imaging (DTI) study revealed the presence of abnormalities in multiple WM tracts that mainly connect the cortices, basal ganglia, thalamus, and brainstem in patients with BSP 16 . However, studies addressing overall changes in WM structural networks in BSP, rather than those observed in specific anatomical regions, are lacking.…”
mentioning
confidence: 99%
“…Nevertheless, a recent DTI study based on 31 BSP patients revealed significant fractional anisotropy (FA) decreases in the white matter of the left anterior lobe of the cerebellum, which was significantly correlated with disease severity (Yang et al, 2014). In addition, our previous study also found widespread white matter abnormalities evaluated by local diffusion homogeneity (LDH) in 29 patients with BSP, which was also significantly correlated with disease severity (Guo et al, 2020). FA, which is one of the most commonly used DTI indexes, quantifies the degree of anisotropy characterized by the random motion of water molecules preferentially directed along the axis of the major axonal pathway, which only reflects diffusion properties within the voxel (Melhem et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
“…We employed the DTI pipeline software PANDA (Pipeline for Analyzing Brain Diffusion Images) 1 to perform DTI data preprocessing ( Cui et al, 2013 ). More detailed information about the DTI data preprocessing can be found in our previous studies ( Liu et al, 2017 ; Guo et al, 2020 ). A total of 68 white matter regions were extracted from the ICBM-DTI-81 white-matter labels atlas (rICBM_DTI_81_WMPM_90p_FMRIB58; Oishi et al, 2008 ) and then we calculated the averaged FA and LDH values of each region using the normalized diffusion parameter maps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation